(untitled) (Biological Sciences - PJSIR, 2022)
Smilax china (China root) has been mostly used in conventional medications for the treatment of numerous ailments. In current study, root extracts and fractions of S. china were assessed for antioxidant, flavonoid, phenol contents, antidiabetic (antiglycation, alpha amylase, acetylcholinesterase inhibition), cytotoxicity (DNA protective, hemolytic tests), thrombolysis and antibiofilm efficacies. The methanolic extract was fractionated into n-butanol, n-hexane, chloroform, ethanol, ethyl acetate solvents along with aqueous fraction. Results indicated that n-hexane had maximum DPPH scavenging potential (34%, P<0.05), while highest flavonoid (22.6 mg CE, P<0.05) and phenols (24.06 mg GAE, P<0.05) were observed in ethyl acetate and n-butanol respectively. Ethanol sample exhibited significant glycation inhibition (70%; P<0.05), whereas methanol and ethanol fractions indicated maximum alpha amylase (29.7%; P<0.05) and acetylcholinesterase (7.49%; P<0.05) inhibitions. Impairment of DNA was blocked by four solvents extracts; i.e. ethanol, ethyl acetate, n-hexane, n-butanol, whereas, n-hexane, aqueous fraction and n-butanol fractions showed optimum antihemolytic (20%), antifibrinolytic (32%) and anti-microbial (58%) potentials. It is recommended that Smilax china has tremendous potential to become a natural medicine supplement. However, it warrants further exploration in clinical trials with animal and human models.